An Analysis of Hegemony in Zootopia Movie - Wirda Fauziah; Yopi Thahara (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
This research is purposed to analyze the structure groups of hegemony and the types of hegemony that happen in Zootopia movie. This research was done using qualitative method. The data were gained by watching the movie, paying attention to the statement and conversation and then analyzed the structures group and the types of hegemony. The data were analyzed by; data reduction, data display and conclusion drawing based on Miles and Huberman‟s theory. The findings of this research reveal that there are two structure gorups of hegemony in Zootopia movie. The first is dominant group that have two parts, civil society and the state. The civil society in Zootopia is the common citizen who did the hegemony toward the weak characters. The state is people who living under system of government who has a power to do hegemony toward the civil society. The second is the subordinate group, the group that dominated by the dominant group. This research also reveals that hegemony in Zootopia movie has two types; coercive control and consensual control. In coercive control, the dominant force the subordinate group to agree and follow their rule while in the consensual control, the dominant influence the subordinate group by their thought to make them follow their rule. In Zootopia movie, coercive power is the dominant and commonly used by the charaters.